2015
DOI: 10.1523/jneurosci.3956-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thinning Explains Changes in Sleep Slow Waves during Adulthood

Abstract: Sleep slow waves (SWs) change considerably throughout normal aging. In humans, SWs are generated and propagate on a structural backbone of highly interconnected cortical regions that form most of the default mode network, such as the insula, cingulate cortices, temporal lobe, parietal lobe, and medial frontal lobe. Regions in this network undergo cortical thinning and breakdown in structural and functional connectivity over the course of normal aging. In this study, we investigated how changes in cortical thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
148
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(172 citation statements)
references
References 53 publications
11
148
5
Order By: Relevance
“…However, older mice showed higher absolute SWA values across the whole recording period, with significant differences compared to the young animals, particularly in the light period and at the end of the dark period. These observations contrast human studies, where absolute SWA values, as well as absolute amplitude, frequency and density of slow waves are found to be decreased in aging123563738.Moreover, the decay rate in SWA in the first three hours after SD was slower in the older mice compared to the young controls. The latter suggests that sleep in older mice is less efficient in dissipating sleep pressure.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, older mice showed higher absolute SWA values across the whole recording period, with significant differences compared to the young animals, particularly in the light period and at the end of the dark period. These observations contrast human studies, where absolute SWA values, as well as absolute amplitude, frequency and density of slow waves are found to be decreased in aging123563738.Moreover, the decay rate in SWA in the first three hours after SD was slower in the older mice compared to the young controls. The latter suggests that sleep in older mice is less efficient in dissipating sleep pressure.…”
Section: Discussioncontrasting
confidence: 84%
“…Since aged mice show increased sleep fragmentation and increased sleep propensity in their habitual waking period during the night as well as less pronounced circadian rhythms of sleep and wakefulness711, they have been considered a good model to investigate age-dependent changes in sleep physiology. In humans, changes in NREM sleep SWA and slow-wave characteristics were studied thoroughly and were found to be consistent with the decrease in the amount of sleep seen in aging123456. However, in mice the effects of age on slow-wave parameters, that could provide insight into cortical network properties, have not been studied, and it remains unknown whether EEG changes occur in parallel with global sleep-wake alterations.…”
mentioning
confidence: 87%
“…Walker and colleagues [69] reported that greater slow wave activity was associated with greater medial PFC gray matter volume (see also [70]). Likewise, Carrier and colleagues [71] found that slow wave density was associated with greater cortical thickness in widespread frontal, temporal, and parietal regions. They concluded that age-related cortical atrophy explains age-related changes in slow wave activity.…”
Section: Structural Neuroimaging Studiesmentioning
confidence: 99%
“…The sleep and neuroimaging correlations reviewed herein disfavor the reduced-sleep-need view, regardless of whether sleep loss causes neural changes [60, 61] or whether neural changes cause sleep loss [47, 71]. Rather than concluding that older adults do not need sleep, if cortical thinning or amyloidal deposition are the cause of older adults’ poor sleep then a more fitting interpretation is that they have lost the ability to sleep in a restorative manner.…”
Section: Neuroimaging Implications For Whether Older Adults Need Sleepmentioning
confidence: 99%
“…Globally, spectral EEG power is reduced during sleep in older adults (Landolt & Borbély, 2001), possibly due to age-related changes in brain morphology (Dubé et al, 2015; Mander et al, 2013). This reduction is especially profound during sleep stages nREM2 and SWS: Older adults have reduced EEG sigma power (a surrogate of spindles) during nREM2 (Mander et al, 2013) and reduced SWA during SWS (Dubé et al, 2015). Given that SWA is influenced by both the number of underlying firing neurons and the synchronicity between these neurons (see review: Greene & Frank, 2010), a reduction in SWA represents the breakdown of these processes.…”
Section: Age-related Changes In Sleepmentioning
confidence: 99%